THE DEVELOPMENT OF SCIENCE PRACTICUM MODULE INTEGRATED STEM ON ENERGY TOPICS USING ETHNOSCIENCE APPROACH - Desi, Yulpita; Putri, Rahmah Evita (Universe, 2024)
Students interest in science learning must be increased by choosing appropriate learning methods so that they can increase students learning motivation and be able to increase students interest in learning. the practicum method that can increase students motivation to learn science. learning with the practicum method will be more meaningful if it is equipped with appropriate teaching materials, namely a practicum module. the practical module will be more functional if the problem taken comes from the students closest environment, namely using an ethnoscience approach and integrated with an approach that triggers students to solve the problem, namely STEM. so this study aims to produce a practical module that is integrated with STEM with the help of a valid and practical etnoscience approach. This type of research is research and development with the ADDIE (Analysis Design Development Implementation Evaluation) development model. The impelmentation and Evaluation stages were not carried out due to time and cost constrains. The research was conducted using an instrument consisting of teacher interview sheets, validity test questionnaires and practicality tests. The research results are processed using the conventional formula in the form of percentages and grouped according to certain categories. The results of the research conducted are the results oh the validity test of the practicum module by the validator of 86% with a very valid category. The two results of the practicality test by the teacher are 99% in the very pratical category and the results of the practicality test by students are 88%. Then the data obtained shows that the development of science practicum module integrated STEM on energy topics using ethnoscience approachis valid and practical.